Cancer pain assessment and management in ambulatory patients at a tertiary hospital in Ghana - Abruquah, Akua A.; Biney, Robert P.; Osei-Bonsu, Ernest B.; Boamah, Kofi M.; Woode, Eric (International Journal Of Community Medicine And Public Health, 2017)
Background: Adequate cancer pain assessment using valid and reliable pain assessment tools is essential for effective cancer pain management. This study evaluated the common types, effectiveness as well as adherence to prescribed analgesics in oncology outpatients in a tertiary oncology centre in Ghana. Methods: This descriptive cross-sectional study involved 204 oncology outpatients with different confirmed cancer diagnosis attending clinic at the Oncology Directorate of a Tertiary Hospital in Ghana. The research instruments used were the medical folders of patients, a hospital-based electronic drug database system; hospital administration management systems (HAMS) and the Brief Pain Inventory Long-Form (BPI-LF). Results: More than half (63.7%) of the participants reported moderate pain, 37.8% received opioid analgesics: 31.4% strong opioids and 6.4% weak opioids. Less than one-fourth (21.6%) had complete pain relief and 18.1% felt they needed a stronger pain medication. A little more than one-fourth (28.4%) of participants took their pain medications 1-2 times per day. Almost half (45.6%) of participants did not experience side effects from taking pain medications and 27.9% needed more information about their pain medications. Conclusions: Enhancing effective cancer symptom management approaches in healthcare practitioners and incorporating existing knowledge and guidelines on cancer pain management into routine clinical practice should be done to enhance efficient pain relief.